2022
DOI: 10.1177/2473011421s00091
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ankle Fractures using Deep Learning Algorithms and Convolutional Neural Network

Abstract: Category: Ankle; Trauma Introduction/Purpose: Early and accurate detection of ankle fractures is crucial for reducing future complications. Radiographs are the most abundant imaging techniques for assessing fractures. We believe deep learning (DL) methods, through adequately trained deep convolutional neural networks (DCNNs), can assess radiographic images fast and accurate without human intervention. In this study, we aimed to assess the performance of two different DCNNs in detecting ankle fractures using ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…5,6,8 Advances in the power of hardware and computing, the development of more accurate imaging techniques, and improvements in the capabilities of software by using computer vision, promise to increase the speed and accuracy of diagnosis and overcome concerns about reliability for the evaluation of images in trauma. 10,11 The widely used complex neural networks have several characteristic features and merits. Compared with conventional machine-learning methods such as decision tree, random forest, boosting, and support vector machines, which are typically used to solve problems in machine-learning on top of structured data, the convolutional filtering operations in a complex neural network can respond to local patterns in features of input which are spatially and temporally correlated.…”
Section: Why Ai and Computer Vision?mentioning
confidence: 99%
“…5,6,8 Advances in the power of hardware and computing, the development of more accurate imaging techniques, and improvements in the capabilities of software by using computer vision, promise to increase the speed and accuracy of diagnosis and overcome concerns about reliability for the evaluation of images in trauma. 10,11 The widely used complex neural networks have several characteristic features and merits. Compared with conventional machine-learning methods such as decision tree, random forest, boosting, and support vector machines, which are typically used to solve problems in machine-learning on top of structured data, the convolutional filtering operations in a complex neural network can respond to local patterns in features of input which are spatially and temporally correlated.…”
Section: Why Ai and Computer Vision?mentioning
confidence: 99%
“…In comparison with previous literature on the use of deep learning for ankle fracture detection, such as the study in 2021 [ 30 ] that achieved high sensitivity and specificity using radiographs, our research contributes to the expanding body of knowledge by exploring the use of CT images and SENet-enhanced ResNet50. The referenced study demonstrated the effectiveness of employing Inception V3 and ResNet50 with radiographs, highlighting the potential of deep learning methods in accurately assessing fractures with high precision.…”
Section: Discussionmentioning
confidence: 93%
“…This approach underscores the diversity of methodologies and imaging modalities that can be leveraged to improve fracture detection. The high performance of DCNNs in the previous study, with sensitivity and specificity reaching up to 98.7% and 98.6% respectively using Inception V3, sets a benchmark for our work and others in the field [ 30 ]. Our findings contribute to this ongoing dialogue by suggesting that enhancements such as SENet can provide significant improvements, particularly in the context of CT-based fracture detection, which presents different challenges and opportunities compared to radiograph-based assessments.…”
Section: Discussionmentioning
confidence: 99%